Detection of a Toxic Methylated Derivative of Phomopsin A Produced by the Legume-Infesting Fungus Diaporthe toxica - Schloß, Svenja; Hackl, Thomas; Herz, Corinna; Lamy, Evelyn; Koch, Matthias; Rohn, Sascha; Maul, Ronald (Journal of natural products (Washington, D.C.), 2017)
Phomopsin A (PHO-A), produced by the fungus Diaporthe toxica, is a mycotoxin known to be responsible for fatal liver disease of lupin-fed sheep. The full spectrum of the toxic secondary metabolites produced by D. toxica is still unknown. PHO-A and the naturally occurring derivatives B–E have been subject to several studies to reveal their structures as well as chemical and toxicological properties. In this work, a methylated derivative (1) of PHO-A isolated from lupin seeds inoculated with D. toxica is described. It was characterized by high-resolution mass and NMR data and shown to be the N-methylated derivative of PHO-A. 1 is cytotoxic against HepG2 cells.